Yeast tRNA3Leu gene transcribed and spliced in a HeLa cell extract. - Standring, D N (1981)
A cloned yeast tRNA3Leu gene containing a 33-base intervening sequence (IVS) is selectively transcribed by a soluble extract from HeLa cells. The 130-nucleotide tRNA3Leu precursor RNA formed is colinear with the gene and contains approximately 4 leader nucleotides and up to 9 trailer nucleotides. The IVS is accurately and efficiently removed by an endogenous HeLa excision-ligase activity to yield the spliced tRNA, the free IVS, and the half-tRNA intermediates. The splicing reaction occurs without prior 5' and 3' maturation of the precursor but, with this exception, this pattern of synthesis and subsequent maturation of the tRNA3Leu precursor conforms to the scheme for tRNA biosynthesis deduced for the xenopus system. Indeed, the two systems utilize similar or identical tRNA3Leu precursors. Our results stress the extraordinary conservation of tRNA biosynthesis in eukaryotes and demonstrate that a HeLa extract provides a useful system for investigating this process.